The instant Internet guide : hands-on global networking - Heslop, Brent D.; Angell, David (Reading, Mass. : Addison-Wesley, 1994)
Before you take off to cruise the vast digital highway called the Internet, it's time for a reality check - roaming the Internet with its congestion, complexity, and hidden potholes requires an informed and equipped traveler. The Instant Internet Guide delivers essential, up-to-date information and hands-on techniques so that anyone, including the lone PC or Mac user, can navigate the Internet and reap the benefits of its resources.
This is the first book on the Internet that explains how to work with the newest and friendliest menu-based programs to perform Internet tasks. Instantly, you'll learn how to deal with service providers and connect to the Internet; follow netiquette guidelines for electronic communications; communicate via e-mail using the menu-based pine program; read, download, and post network news using the handy tin newsreader; remotely log in to online library catalogs, databases, games, and more using the telnet program; mine public file archives using the FTP (file transfer program); find what you need on the Internet using the veronica, archie, gopher, and WAIS programs; master enough basic UNIX commands to speak the native language of the Internet; and locate and visit numerous file archives and interactive sites free of charge.
Read Me First -- Ch. 1. Merging onto the Internet -- Ch. 2. Communicating via Electronic Mail -- Ch. 3. Turning On Network News -- Ch. 4. Interactive Internet -- Ch. 5. Mining Files on the Internet -- Ch. 6. Finding What You Want on the Internet -- Ch. 7. UNIX in About an Hour -- Appendix: Getting a Dial-up Connection to the Internet.
Includes index.
Keywords: Internet